Investigation of an Outbreak of Anemia Cases at an Army Trinitrotoluene Munitions Production Plant From 2004 to 2005 and Subsequent Surveillance 2005–2013. Issue 11 (1st November 2014) - Mallon, Timothy M.; Ortiz, Jose M.; Candler, William H.; Rogers, Gregory; Hillburn, Richard
ABSTRACT: Objective: Investigate an outbreak of anemia that occurred at an Army trinitrotoluene (TNT) munitions production facility in 2004–2005 and describe subsequent medical surveillance efforts between 2005 and 2013. Methods: A retrospective, cross-sectional investigation of anemia cases and exposure levels was conducted to target corrective engineering and administrative changes needed to reduce TNT levels and anemia cases. Results: Mean TNT exposure levels decreased from 1.2 to 0.08 mg/m 3 between 2004 and 2012, but the trend was not statistically significant. Anemia cases rose from 17 to 38 between 2004 and 2011 and cases declined from 4 to 0 between 2012 and 2013. The overall trend in cases was not statistically significant. Conclusions: TNT levels rose at a munitions plant until ventilation changes reduced exposures. Despite this, anemia cases continued to rise until the commander held workers accountable for failing to wear PPE and motivated them to wear respirators to avoid a loss in pay. The case definition of anemia was revised to be consistent with the case definition used by private physicians who practiced in the community. Better coveralls are needed, which are easy to wear, reduce static discharge, and prevent TNT skin absorption.